Implementasi Permainan Tradisional untuk Meningkatkan Intraksi Sosial dan Minat Belajar Peserta Didik Kelas IV SD Negeri 200118 Sadabuan - Lumbantobing, Nur Azizah; Safitri, Adek (LANCAH: Jurnal Inovasi dan Tren, 2024)
Social interaction in children is very important to train so that they can develop. The current challenge is technological advances which can hinder children's social interactions and students' interest in learning, which really needs to be considered in the continuity of students' learning. As is known, students' interest in learning can result in students' lack of focus in participating in learning. Students' lack of focus will also determine students' success in receiving and understanding the material provided by the teacher. Many teachers and schools find students who are interested in learning. Students' lack of interest in learning can be improved by adjusting the learning model according to the child's age, namely those who like to play. The existence of a traditional game-based learning model can increase students' social interaction and interest in learning.